From Caliphates to Climate Crisis: Historical Records, Islamic Teachings, and Environmental Challenges in the Muslim World - Muhammad Adil Iqbal; Nurul Izzati Haji Jamil (Indonesian Journal for Islamic Studies, 2025)
Background of Study: The rise, stability, and demise of many civilizations, including those in the Muslim world, have been profoundly influenced by climate fluctuations, according to historical and modern research. Early Islamic scholars recorded environmental abnormalities and meteorological trends that today offer crucial insights for comprehending contemporary climatic difficulties, especially in areas experiencing drought, water scarcity, and instability brought on by climate change.Aims and scope of paper: This paper looks at how old Islamic writings about the environment, moral lessons from islam, and recent scientific research can be combined to help Muslims better understand and deal with climate change.Methods: The study uses modern scientific research on the effects of climate change in Muslim-majority nations, as well as qualitative analysis of historical documents and Islamic theological texts like the Qur'an, Hadith, and classical jurisprudence.Result: The results show significant similarities between contemporary climate disruptions and historical environmental observations. Additionally, the analysis demonstrates that Islamic ecological ethics provide a cogent moral framework that can facilitate community-based environmental governance, adaptation, and mitigation.Conclusion: The study comes to the conclusion that strengthening faith-based initiatives and improving societal resilience to climate-related hazards in the Muslim world can be achieved by fusing historical Islamic knowledge with modern environmental science.